The Relationship between Milk Fat Content, Vitamin D and Adiposity in Early Childhood. (1st June 2016) - Vanderhout, S; Maguire, J; Birken, C; Parkin, P; Lebovic, G; Chen, Y; O'Connor, D
Abstract: BACKGROUND: Fortified cow's milk is the main dietary source of vitamin D and an important source of dietary fat for North American children. Current guidelines recommend reduced milk fat consumption to reduce childhood obesity, yet the relationship between lower milk fat, vitamin D stores and adiposity is unclear. OBJECTIVES: The objective of this study was to determine the association between percent fat content of milk and both zBMI and 25-hydroxyvi-tamin D; secondly, to explore if volume of milk consumed modified this relationship. DESIGN/METHODS: A cross-sectional study of healthy urban children 12-72 months of age was conducted. Bivariate multiple linear regression was used to test the association between percent milk fat content and child 25-hydroxyvitamin D and zBMI concurrently. The interaction between volume of milk consumed and percent milk fat content was examined to explore how milk volume might modify these relationships. RESULTS: 2745 children were included in the analysis. Percent fat content of milk was positively associated with 25-hydroxyvitamin D (p=0.006), and negatively associated with zBMI (p<0.0001). Children who drank homogenized milk (3.25% fat) had 6.6 nmol/L (95% CI 5.49 to 7.71) higher median 25(OH)D concentration and 0.72 lower (95% CI 0.68 to 0.76) zBMI score than children who drank skim milk (0.1% fat). Volume of milk consumed potentiated the effect of percent fat content of milk on 25-hydroxyvitamin D (p=0.003) but not on zBMI (p=0.77). Children who drank 1 cup of homogenized milk each day had a similar 25-hydroxyvita-min D as children who drank 2.85 cups (95% CI 2.71 to 2.99) of skim milk, but had zBMI score 0.78 (95% CI 0.63, 0.93) units lower. CONCLUSION: Homogenized milk may be more appropriate than reduced fat milk in maximizing serum 25-hydroxyvitamin D and minimizing adiposity in early childhood. Current guidelines for reduced milk fat consumption in childhood may require further study to achieve desired outcomes.